A new index combining thermal, acoustic, and visual comfort of moderate environments in temperate climates. (July 2018) - Buratti, C.; Belloni, E.; Merli, F.; Ricciardi, P.
Abstract: Students spend a lot of time at school, highlighting the great importance of providing comfortable conditions in educational buildings. Indoor environmental conditions are also related to student productivity and well-being, but Literature reviews mainly examine the effects of single parameters on human comfort, lacking in the evaluation of comfort combining different aspects, such as thermal, acoustic, and visual ones. The aim of the paper is to propose an index for the evaluation of the environmental comfort tacking into account thermal, acoustic, and lighting conditions. Seven university classrooms were investigated; measurements of environmental factors were performed including thermal, acoustic, and lighting parameters. Subjective evaluations were also carried out through survey questionnaires purposely elaborated. Three single indexes were proposed basing on the strongest correlation between questionnaire's answer and experimental results: a Predicted Mean Vote Index for the thermo-hygrometric conditions, a Sound Index for the acoustic comfort, and a Visual Index for the lighting conditions. All the indexes are dimensionless and normalized in a 0–1 range: values next to 1 indicate good comfort conditions and values next to 0 indicate bad comfort conditions. On the basis of different weights given for the three aspects, a final combined comfort index was calculated for each classroom and compared with questionnaires results, in order to assess the methodology. Highlights: Analysis of global comfort conditions in seven classrooms was carried out. Data from many questionnaires were collected and compared to experimental results. The questions with the best correlation were selected and used as indexes. A final global index is proposed and compared with questionnaires results. A new questionnaire was developed to improve the study on global comfort.